2007
DOI: 10.1021/jf062900q
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan−Alginate Microcapsules for Oral Delivery of Egg Yolk Immunoglobulin (IgY)

Abstract: Chitosan-alginate microcapsules were evaluated as a method of oral delivery of IgY antibodies. Physical characteristics, encapsulation efficiency (EE%), the loading capacity for IgY (IgY loading percentage, %, w/w of microcapsules), gastro-resistance, and release characteristics of these microcapsules in vitro under varying pH were investigated. Optimum physical factors were established for preparation of homogeneous, spherical, and smooth microcapsules. IgY loading% was not significantly altered by pH of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(72 citation statements)
references
References 25 publications
4
62
0
1
Order By: Relevance
“…Specific IgY against K88+ ETEC was prepared and purified as described previously [3]. IgY powder was obtained by freeze-drying and its purity was determined to be over 82% based on sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific IgY against K88+ ETEC was prepared and purified as described previously [3]. IgY powder was obtained by freeze-drying and its purity was determined to be over 82% based on sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE).…”
Section: Methodsmentioning
confidence: 99%
“…In our previous study, the applicability of chitosan-alginate microcapsules for oral delivery of IgY was established [3]. We showed that chitosan-alginate microcapsulation enabled a larger proportion of the IgY to remain bioactive in a simulated gastrointestinal tract environment providing an effective delivery system for specific IgY.…”
Section: Introductionmentioning
confidence: 99%
“…The use of chitosan-alginate microcapsules to protect IgY from gastrointestinal environment conditions provides significant resistance to pepsin hydrolysis and may enable intact IgY to reach target microorganisms within the lower digestive tract [78]. Another approach protecting IgY from degradation in gastric pH can be the incorporation of antibodies to hydrogel containing acrylamide and acrylic acid with promising results for IgY oral delivery [79].…”
Section: Using Igy For Passive Immunizationmentioning
confidence: 99%
“…The method was modified from Li et al (2007). IgY retention was expressed as the percentage of total available IgY in the microcapsules.…”
Section: Determination Of Igy Retentionmentioning
confidence: 99%